Zasada ne bis in idem w polskim prawie karnym: [The institution of res judicata and the principle of ne bis in idem] (Studia Prawnicze / The Legal Studies, 2007)
Zasady procesu karnego są podstawami, na których opiera się określony model procesu. Nadają procesowi karnemu kształt jednolitego systemu rządzącego się pewnymi ideami przewodnimi, które pozwalają zrealizować postawione przed tym procesem cele. Ułatwiają wykładnię przepisów prawnych lub wskazują kierunek wykładni. Kształtują praktykę wymiaru sprawiedliwości.Czy zakaz ne bis in idem, czyli zakaz prowadzenia kolejnego (powtórnego) postępowania w tej samej sprawie i przeciwko tej samej osobie, po jego prawomocnym zakończeniu, można uznać za zasadę polskiego procesu karnego? The ne bis in idem principle is a guarantee for the accused that he/she will not be held responsible for an act for which he/she has already been tried. This constitutes a fundamental right of the perpetrator of the punishable act, who can demand that proceedings are not commenced, or discontinued if already instituted, if criminal proceedings against him in the same case have already been yalidly terminated.Legal certainty should be ensured eąually for the society in generał and for the individual. Society should have confidence in the legał order in force in a given State.It is generally accepted that the principle of ne bis in idem chiefly serves the protection of persons judged - the sentenced and the acąuitted. This principle also means that proceedings cannot be conducted with the aim of the acąuittal or mitigation of penalty for someone who has been sentenced in a legally valid judgment. However, it should be noted that the ne bis in idem prohibition can, in certain circumstances, be a barrier to demonstrating the innocence of the accused. Hence, it should be noted that modem criminal procedures are mled by the principle of presumed innocence, which can only be set aside by a legally valid court decision declaring guilt of the accused. The accused is considered innocent until his/her guilt has been determined by a legally valid verdict that establishes the ne bis in idem prohibition. Errors madę by the court that have led to the conviction of an innocent person should not be corrected by infringing this principle. Furthermore, legał systems have institutions that allow for setting aside even legally valid sentences.Any natural or legał person whose legał interests have been directly infringed or threatened by a crime can count on a case examination on merits by an independent court. The right of a Citizen to be heard by a court, to a just examination of his/her case by an independent and impartial court established by an act of law, is one of the fundamental human rights provided for in Art. 6 of the European Convention on Protection of Human Rights and Fundamental Freedoms.